Typification of the name Fimbristylis argentea (≡ Scirpus argenteus, Cyperaceae) and notes on its synonyms and reproductive morphology - Majumder, Subrata; Rajak, Pooja; Ghosh, Asok (Phytotaxa, 2026)
Fimbristylis argentea (Rottboll) Vahl (≡ Scirpus argenteus Rottboll) is here lectotypified together with their synonyms using Koenig’s collections. The holotype is also mentioned when applicable. Both the vegetative and reproductive morphology of the species are discussed and compared with recent field collections. Notes are also provided on the typification of other heterotypic synonyms of the species and male reproductive characters.